Understanding Workplace Relationships - LMX quality, Turnover intention and employee job satisfaction, Mediating role of Superior Subordinate Communication - Khan, Sanan Waheed; Omar, Nuredayu (2018)
Workplace relationship is a very vital phenomenon at the workplace. The relationship between a leader & his subordinates can have a major impact on the performance of the employees. The focus of this research is on the relationship between leader-member exchange (LMX), superior subordinate communication (SSC), Turnover intention with employee job satisfaction. This study explores Leader Member Exchange Theory (LMX Theory), which theorizes when leaders and followers have good exchanges or high quality effective LMX relationships, they share mutual trust, feel better, accomplish more, and the overall unit performance within organization is enhanced. It was hypothesized that LMX would directly influence SSC, and SSC would directly influence employee job satisfaction. It was also hypothesized that turnover intention would directly influence employee job satisfaction. Data derived from a self-administered questionnaire, and this will be distributed to employees working in fast food industry of Kedah Malaysia.